Grounds for suspending the execution of a sentence under Article 15 of the Executive Penal Code: Selected issues and case law - Sitnik-Gawlikowska, Katarzyna; Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article addresses the issue of the grounds for suspending the execution of a sentence pursuant to Article 15 of the Executive Penal Code, taking into account selected issues of doctrine and case law. It is a contribution to a deeper analysis of the institution of suspending the execution of a sentence.
Keywords: suspending the execution of a sentence; Executive Penal Code